2022
DOI: 10.3390/ma15062158
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Mechanical Properties of Ti-25Nb-4Ta-8Sn Alloy Prepared by Spark Plasma Sintering

Abstract: As the commercially most-used Ti-6Al-4V alloy has a different modulus of elasticity compared to the modulus of elasticity of bone and contains allergenic elements, β-Ti alloy could be a suitable substitution in orthopedics. The spark plasma sintering (SPS) method is feasible for the preparation of materials, with very low porosity and fine-grained structure, leading to higher mechanical properties. In this study, we prepared quaternary Ti-25Nb-4Ta-8Sn alloy using the spark plasma sintering method. The material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…As the Ta and Nb are β stabilizer elements, a great amount of these phases are found after sintering. The identification of peaks in the X-ray diffraction patterns (Figure 4) corresponding to the different phases were based in previous works of Ti-Ta, Ti-Nb and Ti-Ta-Nb alloys [34][35][36][37][38][39][40]. It was interesting to found that microstructure of samples sintered at 25 °C/min is mostly composed of β-Ti and the martensite phase α''-Ti.…”
Section: Xrd Analysismentioning
confidence: 82%
“…As the Ta and Nb are β stabilizer elements, a great amount of these phases are found after sintering. The identification of peaks in the X-ray diffraction patterns (Figure 4) corresponding to the different phases were based in previous works of Ti-Ta, Ti-Nb and Ti-Ta-Nb alloys [34][35][36][37][38][39][40]. It was interesting to found that microstructure of samples sintered at 25 °C/min is mostly composed of β-Ti and the martensite phase α''-Ti.…”
Section: Xrd Analysismentioning
confidence: 82%
“…The mismatch between the mechanical properties of implant and bone tissue was unsolved. Recently, researchers have begun to focus on new ß titanium alloys (Nadammal et al, 2022;Sing, 2022;Vonavkova et al, 2022). This material can retain the unstable phase, such as the sub-stable ß phase or martensite structure, at room temperature, giving the material good processing plasticity and toughness.…”
Section: Biocompatibility and Osseointegration Properties Of A Novel ...mentioning
confidence: 99%
“…The mismatch between the mechanical properties of implant and bone tissue was unsolved. Recently, researchers have begun to focus on new ß titanium alloys ( Nadammal et al, 2022 ; Sing, 2022 ; Vonavkova et al, 2022 ). This material can retain the unstable phase, such as the sub-stable ß phase or martensite structure, at room temperature, giving the material good processing plasticity and toughness.…”
Section: Introductionmentioning
confidence: 99%